2012
DOI: 10.1080/10888438.2011.570397
|View full text |Cite
|
Sign up to set email alerts
|

Do Poor Readers Feel Angry, Sad, and Unpopular?

Abstract: We investigated whether being poorly skilled in reading contributes to children’s self-reported feelings of anger, distractibility, anxiety, sadness, loneliness, and social isolation. Data were analyzed from a longitudinal sub-sample of children (N=2,751) participating in the Early Childhood Longitudinal Study—Kindergarten Cohort. Multi-level logistic regression analyses indicated that poor readers in 3rd grade were more likely to consider themselves as angry, distractible, sad, lonely, and unpopular in 5th gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 82 publications
2
50
0
1
Order By: Relevance
“…Poor reading achievement has been theorized to result in children experiencing increasingly generalized deficits in their socio-emotional adjustment (Stanovich, 1988), particularly as their lack of reading proficiency becomes evident to their peers thus leading to feelings of isolation and interpersonal hostility (Chapman, 1988). Although causal relationships cannot be established based on our correlational analyses, the obtained findings are consistent with prior work indicating a largely unidirectional pathway from reading to behavioral difficulties in the general population of U.S. schoolchildren (e.g., Lin et al, 2013; Morgan, Farkas, & Maczuga, 2012; Morgan, Farkas, Tufis, & Sperling, 2008) and indicate that poor reading may be predictive of impaired socioemotional functioning in children with ADHD.…”
Section: Discussionsupporting
confidence: 89%
“…Poor reading achievement has been theorized to result in children experiencing increasingly generalized deficits in their socio-emotional adjustment (Stanovich, 1988), particularly as their lack of reading proficiency becomes evident to their peers thus leading to feelings of isolation and interpersonal hostility (Chapman, 1988). Although causal relationships cannot be established based on our correlational analyses, the obtained findings are consistent with prior work indicating a largely unidirectional pathway from reading to behavioral difficulties in the general population of U.S. schoolchildren (e.g., Lin et al, 2013; Morgan, Farkas, & Maczuga, 2012; Morgan, Farkas, Tufis, & Sperling, 2008) and indicate that poor reading may be predictive of impaired socioemotional functioning in children with ADHD.…”
Section: Discussionsupporting
confidence: 89%
“…However, the lower quality of their language communication results in unsuccessful social interaction with their peers, and so increases the risk for the development of internalized socioemotional pathology, including social withdrawal, anxiety, and depression (Rourke, Young, & Leenaars, 1989). Some studies have supported this hypothesis of a causal relation between mathematics difficulties and internalizing behavior problems (Greenham, 1999; Morgan et al, 2012; White, Moffitt, & Silva, 1992). Consequently, at least part of the observed co-occurrence between reading and behavioral difficulties may instead result from impaired non-verbal processes involved in mathematics learning as indicated by mathematics difficulties.…”
Section: Theoretical Explanations Of the Co-occurrence Between Readinmentioning
confidence: 92%
“…It is therefore unclear to what extent reading, mathematics, and behavioral difficulties inter-relate in the more general population of U.S. schoolchildren. Few studies have included a prior history of mathematics difficulties as another potential explanatory variable when investigating the co-occurrence of reading and behavioral difficulties (Morgan et al, 2012), despite it constituting a strong possible confound of the observed co-occurrence. Additionally, many existing studies failed to control for either earlier reading problems or behavior problems (Hinshaw, 1992) or did not include other potentially relevant variables in their analyses (Fleming, Harachi, Cortes, Abbott, & Catalano, 2004).…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 2 more Smart Citations